P6 Menthol Has Beneficial Effects In The Airways Through A Trpm8-independent Mechanism. (10th November 2014) - Maher, SA; Birrell, MA; Bonvini, SJ; Wortley, MA; Dubuis, ED; Shala, F; Jones, VC; Flajolet, P; Negreskul, Y; Britton, Z; Hebib, L; Belvisi, MG
Abstract : Introduction: Asthma is a debilitating disease of the airways characterised by symptoms such as bronchoconstriction, hyperresponsiveness and cough. Current therapies are associated with significant side effects and are ineffective in severe disease highlighting the need for novel treatments. Menthol, a cooling compound found in medicinal products, is commonly thought to activate the thermo-sensing cation-permeable Transient Receptor Potential Melastatin 8 (TRPM8) channel. Furthermore, menthol is known for its beneficial effects in the airways such as bronchodilation 1 and suppression of nerve activation and cough, 2 however the mechanism of action is unknown. Aim: To pharmacologically characterise the role of TRPM8 and menthol in the airways. Methods: TRPM8 gene expression was measured using Taqman real-time PCR. Mouse and guinea pig isolated vagal nerves were mounted in a grease-gap chamber and depolarisation (mV) recorded as an indicator of sensory nerve activity. Segments of murine and guinea pig trachea were attached to a force transducer in an organ bath and relaxation of carbachol-induced tone recorded (mg). Results: TRPM8 is expressed in mouse and guinea pig vagal ganglia. The selective TRPM8 agonist, WS3, caused activation of guinea pig and mouse isolated vagal nerves, which was inhibited by the TRPM8 antagonist, JNJ41876666. Furthermore, WS3-induced depolarisation was abolished in isolated vagal nerves from Trpm8 -/- mice. (-)-menthol (active form) caused a small depolarisation of mouse and guinea pig isolated vagal nerves, which was blocked by JNJ41876666. Interestingly, pre-incubation of (-)-menthol inhibited vagal nerve activation induced by the tussive stimulus, capsaicin, an effect that was not inhibited by JNJ41876666. WS3 and (-)-menthol caused a concentration-dependent relaxation of murine and guinea pig trachea, which was not abolished by JNJ41876666 nor in the Trpm8 -/- mouse airway. No expression of TRPM8 was detected in guinea pig or mouse airway smooth muscle. Conclusions: (-)-menthol caused a small TRPM8-dependent activation but a robust TRPM8-independent inhibition of vagal sensory nerve activity and relaxation of airway smooth muscle. Elucidating the mechanism behind the beneficial effects of (-)-menthol could lead to the development of promising new therapeutic targets for airway diseases such as asthma. References: Ito et al. Pulm Pharmacol Ther 2008;21(5):812–817 Plekova et al. J Appl Physiol 2013;115(2):268–274